2013
DOI: 10.1002/bjs.8911
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of laparoscopic versus open cholecystectomy for patients with liver cirrhosis and symptomatic cholecystolithiasis

Abstract: Patients with CTP grade A or B liver cirrhosis who undergo LC for symptomatic cholecystolithiasis have fewer overall postoperative complications, a shorter hospital stay and resume a normal diet more quickly than those who undergo OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 33 publications
1
66
0
8
Order By: Relevance
“…Number of blood transfusions required had no statistically significant difference between the two groups (P = 0.06). Time to resume a normal diet was significantly shorter in the laparoscopic group (P ≤ 0.001) [35].…”
Section: Laparoscopic Cholecystectomy In Cirrhoticsmentioning
confidence: 92%
“…Number of blood transfusions required had no statistically significant difference between the two groups (P = 0.06). Time to resume a normal diet was significantly shorter in the laparoscopic group (P ≤ 0.001) [35].…”
Section: Laparoscopic Cholecystectomy In Cirrhoticsmentioning
confidence: 92%
“…Five systematic reviews comparing outcomes of open cholecystectomy (OC) versus LC for symptomatic cholelithiasis in Child-Pugh A or B cirrhotic patients, show fewer overall postoperative complications, shorter hospital stay, shorter operative time and faster resumption of a regular diet for the LC group [84][85][86][87][88][89] (LE1). Due to the high risk of liver failure and dangerous hemorrhage in Child-Pugh C patients, surgery should be avoided [90].…”
Section: Cirrhosismentioning
confidence: 99%
“…1,2 Even after LC, however, many patients complain of pain in the shoulder, back, and abdomen; thus, reducing postoperative discomfort after LC is an area of active research. 3 Many authors have studied various techniques, and systematic reviews have confirmed the feasibility of methods such as low-pressure pneumoperitoneum and intraperitoneal instillation of saline to reduce pain.…”
Section: Introductionmentioning
confidence: 99%